THE EVALUATION OF FROZEN SEMEN PRODUCTION POTENTIAL IN ETAWAH GRADE AND ANGLO-NUBIAN BREEDS (Evaluasi Potensi Produksi Semen Beku pada Kambing Peranakan Etawah dan Anglo Nubian) - Casmuti Casmuti; Mokhamad Fakhrul Ulum; Syahruddin Said; Taufiq Purna Nugraha; Asep Kurnia; Raden Iis Arifiantini (Universitas Nusa Cendana, 2026)
This study aimed to evaluate the potential of frozen semen production in Etawah Grade and Anglo-Nubian breeds based on fresh semen characteristics and to assess variations among individuals and breeds. The research was conducted at the Lembang Artificial Insemination Center, West Bandung, using primary data from five ejaculations per individual and secondary data from the year 2024. Fresh semen was evaluated for semen volume, sperm motility, and sperm concentration, reflecting the number of straws that can be produced per ejaculation. Frozen semen production potential was calculated based on semen volume, sperm motility, and sperm concentration. The results showed significant differences (P<0.01) in production potential among individuals and between breeds. The highest production potential was observed in the buck named Andromeda (122.45 ± 2.07 straws), which was significantly higher than that of other individuals. Anglo-Nubian breed showed a higher production potential (105.76 ± 2.54 straws) compared to Etawah Grade (91.63 ± 1.92 straws). However, Etawah Grade bucks exhibited relatively better sperm motility. In conclusion, both individual and breed factors significantly influence frozen semen production potential. Anglo-Nubian bucks have higher production capacity, while Etawah Grade bucks may offer better sperm quality. These findings provide important insights for optimizing breeding strategies and semen production planning in artificial insemination programs.